Comparison of liver stiffness assessment by transient elastography and shear wave elastography using six ultrasound devices. Issue 6 (5th March 2019) - Iijima, Hiroko; Tada, Toshifumi; Kumada, Takashi; Kobayashi, Natsuko; Yoshida, Masahiro; Aoki, Tomoko; Nishimura, Takashi; Nakano, Chikage; Ishii, Akio; Takashima, Tomoyuki; Sakai, Yoshiyuki; Aizawa, Nobuhiro; et al.
Abstract : Aim: Transient elastography (TE) is the gold standard for measurement of liver stiffness. The usefulness of shear wave elastographies (SWE) is well accepted. However, the measurement values cannot be equivalently compared because cut‐off values for the diagnosis of liver fibrosis are different among those devices. We aimed to clarify correlations, to generate the regression equations between TE and SWEs, and to compare the diagnostic ability of each device to diagnose liver fibrosis. Methods: A total of 109 patients with chronic liver disease who underwent liver biopsy and same‐day evaluation of liver stiffness using six ultrasound devices were analyzed. The diagnostic ability of liver stiffness from each ultrasound device and correlations between TE and each SWE were analyzed. Results: Liver stiffness measured by all six ultrasound devices increased significantly as liver fibrosis stage advanced ( P  < 0.001). Receiver operating characteristic (ROC) curve analysis for predicting significant fibrosis (≥F2) and cirrhosis yielded area under the ROC curve (AUROC) values based on TE of 0.830 (95% confidence interval [CI], 0.755–0.905) and 0.959 (95% CI, 0.924–0.995), respectively. The AUROCs for predicting significant fibrosis (≥F2) and cirrhosis (F4) based on SWE from all five ultrasound devices were over 0.8 and 0.9, respectively. Furthermore, the correlation coefficients between TE values and SWE values from five ultrasound devices were all over 0.8, indicating a strong relationship. Conclusion: Our study showed strong correlations between TE and SWEs with high correlation coefficients. The regression equations between TE and SWEs demonstrated the ability to compare the measurement values in each device equivalently.